Deriva de glyphosate e carfentrazone-ethyl sobre a severidade da ferrugem (Puccinia psidii) em clones de Eucalyptus grandis - Samuel Alves dos Santos (2016)
The action of herbicides could affect the severity level of rust (Puccinia psidii) of eucalyptus. The present study aimed to: (i) assess the tolerance of the eucalyptus clones to carfentrazone-ethyl and glyphosate; (ii) assess the severity of rust; (iii) evaluate the effects of the herbicides in anatomy and leaf ultrastructure and physiology of clones; and (iv) evaluate the histopathology of host-pathogen interaction. For installation the experiments were used two Eucalyptus grandis clones, one resistant (G-21), and other susceptible (G-33) to fungus P. psidii. The herbicides doses tested were zero, 86.4 g a.e. ha-1 of glyphosate, 3.0 g a.e. ha-1 of carfentrazone-ethyl and mixture (86.4 g a.e. ha-1 of glyphosate + 3.0 g a.e. ha-1 of carfentrazone-ethyl). Two days after application (DAA) of herbicides, was performed the inoculation of the pathogen. For anatomical and ultrastructural analysis, leaf samples were collected at: zero; 6; 24: 21 days after inoculation (DAI). The photosynthetic rate, stomatal conductance and the effective yield of photosystem II were evaluated at 4 and 23 DAA. The tolerance of the eucalyptus clones to herbicides and rust severity were assessed at the end of the experiments (23 DAA and DAI 21, respectively). Plants of the two clones showed changes in leaf anatomy, as erosion of epicuticular waxes, degeneration of epidermal cells and parenchyma, especially when exposed to application of carfentrazone-ethyl and mixture. In addition, plants exposed to herbicide application showed an accumulation of starch granules in the chloroplasts. The G-33 clone was the most affected, with higher phytotoxicity, lower growth, lower dry matter production and greater reduction of physiological parameters, when treated with the herbicide mixture, followed by single doses of carfentrazone-ethyl and glyphosate, respectively. The growth, development and physiological parameters of the G-21 clone were not affected by the single dose of carfentrazone-ethyl. The disease occurred only in clone susceptible to P. psidii. The plants of G-33 clone, exposed to herbicides had lower disease severity. At 6 DAI, plants of this clone, that were exposed to herbicide application, showed below the point of infection, layers of parenchyma cells with intensive cell division, plus a "pre-pustule" with reduced development when it compared to the control plants. At 12 DAI, the pustules were fully formed and with great production of urediniospores in control plants. However, plants exposed to the herbicides application presented, below the point of infection, compartmentalization fabric with two until four layers, limiting the area colonized by the fungus, and pustules with no or reduced production of spores. The phytointoxication and the reduction in photosynthetic rate, due to herbicide action, are correlated with the decrease on severity of rust in the G-33 clone. In summary, it is concluded that G-33 clone is more sensitive to herbicides. And that the drift of the herbicides (glyphosate and carfentrazone-ethyl), applied alone or in mixture, does not alter the level of resistant of the G-21 clone. However, reducing the rust severity of de Eucalyptus in the plants of the susceptible clone (G-33), especially when used in mixture.